Catastrophic costs of tuberculosis care in a population with internal migrants in China - Liping Lu; Qi Jiang; Jianjun Hong; Xiaoping Jin; Qian Gao; Heejung Bang; Kathryn DeRiemer; Chongguang Yang (BMC, 2020)
Abstract Background The internal rural-to-urban migration is one of the major challenges for tuberculosis (TB) control in China. Patient costs incurred during TB diagnosis and treatment could cause access and adherence barriers, particularly among migrants. Here, we estimated the prevalence of catastrophic costs of TB patients and its associated factors in an urban population with internal migrants in China. Methods A cross-sectional survey was conducted to enroll culture-confirmed pulmonary TB patients in Songjiang district, Shanghai, between December 1, 2014, and December 31, 2015. Consenting participants completed a questionnaire, which collected direct and indirect costs before and after the diagnosis of TB. The catastrophic cost was defined as the annual expenses of TB care that exceeds 20% of total household disposable income. We used logistic regression to identify factors associated with catastrophic costs. Results Overall, 248 drug-susceptible TB patients were enrolled, 70% (174/248) of them were from migrants. Migrant patients were significantly younger compared to resident patients. The total costs were 25,824 ($3689) and 13,816 ($1974) Chinese Yuan (RMB) in average for resident and migrant patients, respectively. The direct medical cost comprised about 70% of the total costs among both migrant and resident patients. Overall, 55% (132 of 248) of patients experienced high expenses (>10% of total household income), and 22% (55 of 248) experienced defined catastrophic costs. The reimbursement for TB care only reduced the prevalence of catastrophic costs to 20% (49 of 248). Meanwhile, 52% (90 of 174) of the internal migrants had no available local health insurance. Hospitalizations, no available insurance, and older age (> 45-year-old) contributed significantly to the occurrence of catastrophic costs. Conclusions The catastrophic cost of TB service cannot be overlooked, despite the free policy. Migrants have difficulties benefiting from health insurance in urban cities. Interventions, including expanded medical financial assistance, are needed to secure universal TB care.